Learning Anxiety in the Language Classroom - Zybert, Jerzy (Glottodidactica, 2006)
It has generally been acknowledged that anxiety is an affective factor that plays a significant role in any learning. A highly specific type of anxiety, foreign language classroom learning anxiety, has been distinguished and recognised as quite common among foreign language learners (Horwitz et al. 1991). The article provides some theoretical considerations related to the issue and presents findings from research on it conducted among Polish secondary school students of English. Conclusions include some practical suggestions for language teachers.